Diversification of foreign trade in Veracruz: opportunities in Southeast Asia - Aníbal Carlos Zottele Allende; Abigail Vázquez Morales; Érika Irais Benítez Arcos (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2017)
Mexican exports, and specifically those of the State of Veracruz, are mainly channeled into the United States of America.